2013
DOI: 10.1088/0256-307x/30/6/067803
|View full text |Cite
|
Sign up to set email alerts
|

The Surface Photovoltaic and Photoluminescent Evolution of a Silicon Nanoporous Pillar Array for Different Etching Times

Abstract: A series of silicon nanoporous pillar array (Si-NPA) samples are prepared with different times of hydrothermal etching, and their surface morphologies are characterized. A systematic study on the evolution trend of the surface photovoltage and photoluminescence spectra discloses that the adoption of a prolonged etching time will increase the native degree of oxidation and decrease the interfacial states density localized in the SiOš‘„ matrix. These results might be helpful for designing Si-NPA-based semiconduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…[19āˆ’25] In the SPV method, the illumination-induced changes in the surface potential of the semiconductor are measured by a nondestructive and noncontact method. [19,20] In our previous work, [26] it was found that the SPV spectrum of Si-NPA is obviously different to that of single crystal silicon (sc-Si) and the SPV mechanism of Si-NPA needs to be further clarified. In this Letter, the SPV properties of the Si-NPA sample are studied first by using SPV spectroscopy.…”
mentioning
confidence: 97%
“…[19āˆ’25] In the SPV method, the illumination-induced changes in the surface potential of the semiconductor are measured by a nondestructive and noncontact method. [19,20] In our previous work, [26] it was found that the SPV spectrum of Si-NPA is obviously different to that of single crystal silicon (sc-Si) and the SPV mechanism of Si-NPA needs to be further clarified. In this Letter, the SPV properties of the Si-NPA sample are studied first by using SPV spectroscopy.…”
mentioning
confidence: 97%